From consumption to over-consumption: Didier de Chousy’s Ignis (1883), or, when the earth house is on fire (Colloquia Comparativa Litterarum, 2025)
This article deals with an underrated novel by Didier de Chousy, Ignis (1883), published during the craze for scientism and positivism. This anticipation novel, fraught with grating irony, went against the optimism that defined the craze, as the author used the boundless technical possibilities flaunted by the industrial age to imagine a robot-assisted “augmented humanity”. Utopia was thus turned into scathing social dystopia and, a few years before Jules Verne’s novel, a “topsy-turvy” world on the brink of self-destruction was depicted. This ground-breaking work, which tackled both social criticism and the need for environmental awareness, heralded many of the themes that inspired H. G. Wells and the “brave new world” Chousy imagined was just as relevant as the ones of our modern dystopias: the model of development that largely remains ours found itself relentlessly questioned, as a call for immediate change was issued.
Keywords: Chousy (Didier de); social dystopia; whistle-blowing literature; Capitalocene; Anthropocene; progress (criticism of)